Temporal patterns of radial growth in declining Austrocedrus chilensis forests in Northern Patagonia: The use of tree-rings as an indicator of forest decline - Amoroso, Mariano Martin (2012)
Using dendrochronology, combined with tree- and stand-level information, we reconstructed the temporal dynamics of ‘mal del ciprés’, a widespread decline of Austrocedrus chilensis forests in Argentina. We developed 12 new site-specific ring-width chronologies representing the growth of trees with no external (crown) or internal (radial growth) symptoms of decline. By comparing the ring-width series of individual trees with these reference chronologies, we detected reduced radial growth, likely due to ‘mal del ciprés’, in 301 symptomatic and dead overstory trees out of 1082 sampled trees. Radial growth decline also occurred in 67 living trees with asymptomatic crowns providing evidence that radial growth decline can be an early indicator of ‘mal del ciprés’. The length of the radial growth decline averaged 27 years for all trees and was 29 and 22 years for living symptomatic and dead overstory trees, respectively; the maximum decline length was 80 years. At the site level, the onset of radial growth decline ranged from the early 1920s to the 1960s, preceding dates reported in historical records. By 1979, P75% of trees per site exhibited radial growth decline. We conclude that decline in radial growth precedes crown symptoms in at least some A. chilensis trees in forests with ‘mal del ciprés’. Reduced radial growth prior to external crown symptoms implies that water uptake had been reduced, possibly because of root damage from Phyophthora or drought or their interactions. It also suggests salvage harvests that aim to eradicate trees with crown symptoms and facilitate growth of residual trees may not be the most effective management response to ‘mal del ciprés’.